Oxygenation improvement and duration of prone positioning are associated with ICU mortality in mechanically ventilated COVID-19 patients - Silvia De Rosa; Nicolò Sella; Giacomo Bellani; Giuseppe Foti; Andrea Cortegiani; Giulia Lorenzoni; Dario Gregori; Annalisa Boscolo; Lucia Cattin; Muhammed Elhadi; Giorgio Fullin; Eugenio Garofalo; et al. (Annals of Intensive Care)
Abstract Background Prone position has been diffusely applied in mechanically ventilated COVID-19 patients. Our aim is ascertaining the association between the physiologic response and the length of the first cycle of prone position and intensive care unit (ICU) mortality. Methods International registry including COVID-19 adult patients who underwent prone positioning. We measured the difference for arterial partial pressure of oxygen to inspired fraction of oxygen ratio (PaO2/FiO2), ventilatory ratio, and respiratory system compliance (Crs) between baseline supine position and at either the end of the first cycle of prone position (Delta-PP) or re-supination (Delta-PostPP). Results We enrolled 1816 patients from 53 centers. Delta-PP and Delta-PostPP for PaO2/FiO2 were both associated with ICU mortality [OR (95% CI) 0.48 (0.38, 0.59), and OR (95% CI) 0.60 (0.52, 0.68), respectively]. Ventilatory ratio had a non-linear relationship with ICU mortality for Delta-PP (p = 0.022) and Delta-PostPP (p = 0.004). Delta-PP, while not Delta-PostPP, for Crs was associated with ICU mortality [OR (95% CI) 0.80 (0.65, 0.98)]. The length of the first cycle of prone position showed an inverse relationship with ICU mortality [OR (95% CI) 0.82 (0.73, 0.91)]. At the multivariable analysis, the duration of the first cycle of prone position, Delta-PP and Delta-PostPP for PaO2/FiO2, and Delta-PostPP for ventilatory ratio were independently associated with ICU mortality. Conclusion In COVID-19 patients with acute respiratory failure receiving invasive mechanical ventilation and prone positioning, the physiological response to prone position is associated with ICU mortality. Prolonging the duration of the first cycle of prone position is associated with improved survival.